2021
DOI: 10.1016/j.ihj.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concomitant respiratory infections in the management and outcomes acute myocardial infarction-cardiogenic shock

Abstract: Objective To evaluate the prevalence and impact of respiratory infections in cardiogenic shock complicating acute myocardial infarction (AMI-CS). Methods Using the National Inpatient Sample (2000–2017), this study identified adult (≥18 years) admitted with AMI-CS complicated by respiratory infections. Outcomes of interest included in-hospital mortality of AMI-CS admissions with and without respiratory infections, hospitalization costs, hospital length of stay, and disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
0
1
Order By: Relevance
“…But in contrast to the earlier literature ndings and the ones in our study, Parenica et al (2017) found no signi cant difference in mortality between infected and non-infected acute MI patients admitted with cardiogenic shock [30]. In fact, Patlolla et al (2021) in their recent published article observed lower in-hospital mortality rate in acute myocardial infarction and cardiogenic shock patient complicated by respiratory infection compared to those with no infections, as well as lower utilization of coronary angiography and PCI which was attributed to higher rates NSTEMI-CS and lower rates of STEMI-CS in admissions with respiratory infections compared to those without [31].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…But in contrast to the earlier literature ndings and the ones in our study, Parenica et al (2017) found no signi cant difference in mortality between infected and non-infected acute MI patients admitted with cardiogenic shock [30]. In fact, Patlolla et al (2021) in their recent published article observed lower in-hospital mortality rate in acute myocardial infarction and cardiogenic shock patient complicated by respiratory infection compared to those with no infections, as well as lower utilization of coronary angiography and PCI which was attributed to higher rates NSTEMI-CS and lower rates of STEMI-CS in admissions with respiratory infections compared to those without [31].…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 100 patients developed sputum infection, and the duration of stay for these patients were on average 15.3 days, which is more than double the duration spent by MI patients without any infections (6 days). These results were in line with those found in previous studies demonstrating that indeed MI admissions with concomitant respiratory infection presenting with in uenza [29] or with cardiogenic shock [31] have longer hospital stay and higher cost compared to those with no respiratory infections. Duration of hospital stay for patient with concomitant respiratory infection was slightly lower than those with bloodstream infections but higher than those with wound infections (45 patients averaging 12.0 days) and urine infections (113 patients averaging 11.7 days).…”
Section: Discussionsupporting
confidence: 93%